An autonomous rail-road amphibious robotic system for railway maintenance using sensor fusion and mobile manipulator - Liu, Haochen; Rahman, Miftahur; Rahimi, Masoumeh; Starr, Andrew; Durazo-Cardenas, Isidro; Ruiz-Carcel, Cristobal; Ompusunggu, Agusmian Partogi; Hall, Amanda; Anderson, Robert (Elsevier, 2023)
The current maintenance of railway infrastructure replies heavily on human involvement, requiring possession of the track section during maintenance, resulting in high costs and inefficient execution. This paper proposes an autonomous rail-road amphibious robotic system for railway inspection and maintenance tasks. By virtue of its road and rail-autonomous mobility, it is able to execute the complete maintenance execution flow in multiple phases. The system provides flexible track job location access, low-cost maintenance execution, and reduced track network possession. The payload mobile manipulator and sensor fusion enhance the system's capabilities for multiple types of inspection and repair. The design of a command and control system was guided by a rule-based expert system strategy to enable remote operation of the whole system. The developed demonstrator of a track wheel accompanied unmanned ground vehicle was integrated and demonstrated in both operational and realistic track environments with multiple testing activities of remote operation, navigation, accurate job detection, inspection, and repair, confirming effective job completion and logical human interaction. The proposed method produces an outstanding hardware-software integrated robotic inspection and repair system with a high level of technological readiness for autonomous railway maintenance and intelligent railway asset management.
Keywords: Railway maintenance; Autonomous robotic system; Command and control; System design; Information fusion